Expression of Prostanoid EP3 Receptors in Oral Squamous Epithelium and Oral Squamous Cell Carcinoma. (9th February 2015) - Kashif, Muhammad; Ishfaq, Muhammad; Nagi, A. H.
Abstract : Objectives . To carry out a descriptive analysis of the expression of the EP3 receptors of PGE2 in different histological grades of OSCC and adjacent normal epithelium. Material and Methods . A total of 46 patients presenting with various histological subtypes and grades of OSCC were recruited from Maxillofacial Surgery Department of Nishtar Institute of Dentistry Multan. Microscopically tumour subtyping and histological grading according to Anneroth's grading system were carried out. Immunohistochemical staining with rabbit polyclonal EP3 receptor antibody was performed and sections were scored for intensity and proportion of positive adjacent squamous epithelial and tumour cells. Results . Out of 46 patientsn = 28 (60.9%) were well differentiated, n = 15 (32.6%) were moderately differentiated, and onlyn = 3 (6.5%) were poorly differentiated. Alln = 46 cases of OSCC were positive for EP3 receptor antibody, n = 14 (30.4%) cases had strong intensity of anti EP3 antibody staining in tumour tissue, n = 17 (37%) cases showed moderate intensity, andn = 15 (32.6%) cases showed weak intensity. Conclusion . Prostanoid EP3 receptors are widely but variably expressed in OSCC. Most of well differentiated OSCC cases show a moderate to strong expression of EP3 receptors. However, insignificant statistical relation to histological grades of OSCC has been observed. This might be due to small sample size of the study.